Co-based alloys and their powders

A Co-based alloy with optimized C, Cr, W, Si, Mn, Fe, and Ni composition, along with controlled ε phase and carbides, addresses toughness and hardness issues, resulting in compacted materials with enhanced corrosion resistance and mechanical properties.

JP7602328B2Active Publication Date: 2024-12-18SANYO SPECIAL STEEL CO LTD
View PDF 13 Cites 0 Cited by

Patent Information

Application Number
JP2020107983
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-06-23
Publication Date
2024-12-18
Estimated Expiration
2040-06-23

AI Technical Summary

Technical Problem

Existing Co-based alloys suffer from insufficient toughness and hardness, as noted in JP-A-2001-288521 and JP-A-2016-7632.

Method used

A Co-based alloy composition comprising specific ranges of C, Cr, W, Si, Mn, Fe, Ni, and optionally Cu or Mo, with controlled volume fractions of ε phase and carbides, optimized for a balanced matrix and dispersed carbides to enhance corrosion resistance, toughness, and hardness.

Benefits of technology

The alloy achieves excellent corrosion resistance, toughness, and hardness, as demonstrated by the production of compacted materials with improved mechanical properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007602328000001
    Figure 0007602328000001
  • Figure 0007602328000002
    Figure 0007602328000002
  • Figure 0007602328000003
    Figure 0007602328000003
Patent Text Reader

Abstract

To provide a Co-based alloy that can give a molding having excellent corrosion resistance.SOLUTION: A Co-based alloy contains C: 1.00 mass% or more and 3.00 mass% or less, Cr: 25.0 mass% or more and 34.0 mass% or less, W: 3.0 mass% or more and 15.0 mass% or less, Si: 0.01 mass% or more and 2.00 mass% or less, Mn: 0.01 mass% or more and 1.00 mass% or less, Fe: 10.0 mass% or less and Ni: 15.0 mass% or less. The Co-based alloy further contains Cu: 0.1 mass% or more and 10.0 mass% or less and / or Mo: 0.1 mass% or more and 15.0 mass% or less. The balance is Co and inevitable impurities.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a Co-based alloy suitable for methods such as melting, powder metallurgy, powder cladding, laser cladding, and powder extrusion. [Background technology]

[0002] Co-based alloys generally have excellent corrosion resistance, and various improvements on these Co-based alloys have been proposed.

[0003] JP 2001-288521 A discloses a Co-based alloy containing C, Si, Cr, W, Fe, Ni, Mo, and W. In the metal microstructure of this Co-based alloy, eutectic carbides are dispersed in a matrix. The eutectic carbides are granular or lumpy. The grain size of the eutectic carbides is 30 μm or less. This metal structure is achieved by plastic working. This Co-based alloy has excellent corrosion resistance and wear resistance.

[0004] JP 2016-7632 A discloses a Co-based alloy containing Ni, Mn, Fe, C, Si, Cr, and Mo. These elements can contribute to cavitation erosion resistance. These elements can also contribute to toughness. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2001-288521 A [Patent Document 2] JP2016-7632A Summary of the Invention [Problem to be solved by the invention]

[0006] The Co-based alloy disclosed in JP 2001-288521 A has insufficient toughness, and the Co-based alloy disclosed in JP 2016-7632 A has insufficient hardness.

[0007] An object of the present invention is to provide a Co-based alloy from which a molded product having excellent corrosion resistance, toughness and hardness can be obtained. [Means for solving the problem]

[0008] The Co-based alloy according to the present invention has C: 1.00% by mass or more and 3.00% by mass or less, Cr: 25.0 mass% or more and 34.0 mass% or less, W: 3.0% by mass or more and 15.0% by mass or less, Si: 0.01% by mass or more and 2.00% by mass or less, Mn: 0.01% by mass or more and 1.00% by mass or less, Fe: 10.0% by mass or less and Ni: 15.0% by mass or less The Co-based alloy further comprises Cu: 0.1% by mass or more and 10.0% by mass or less and / or Mo: 0.1% by mass or more and 15.0% by mass or less The balance is Co and unavoidable impurities.

[0009] Preferably, the volume fraction Pε of the ε phase having an hcp structure relative to the entire metal structure of this Co-based alloy is 60.0% or less.

[0010] The metal structure of this Co-based alloy is as follows: (1) Matrix and (2) Carbides dispersed in this matrix This matrix (1) has the following structure: (1-1) γ phase, which has an fcc structure and / or (1-2) ε phase, which has the hcp structure The carbide (2) includes (2-1) M6C carbide (2-2)M7C3 carbide and (2-3)M23C6 carbide The metal structure preferably includes one or more selected from the group consisting of: Preferably, the volume fraction Pc of carbides relative to the entire metal structure is 12.0% or more and 50.0% or less.

[0011] In another aspect, the powder material according to the present invention is a Co-based alloy. C: 1.00% by mass or more and 3.00% by mass or less, Cr: 25.0% by mass or more and 34.0% by mass or less, W: 3.0% by mass or more and 15.0% by mass or less, Si: 0.01 mass% or more and 2.00 mass% or less, Mn: 0.01% by mass or more and 1.00% by mass or less, Fe: 10.0% by mass or less and Ni: 15.0% by mass or less The Co-based alloy further comprises Cu: 0.1 mass% or more and 10.0 mass% or less and / or Mo: 0.1% by mass or more and 15.0% by mass or less The balance is Co and unavoidable impurities. Effect of the Invention

[0012] The compact obtained from the Co-based alloy according to the present invention is excellent in corrosion resistance, toughness and hardness. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] Hereinafter, the present invention will be described in detail based on preferred embodiments with reference to the drawings as appropriate.

[0014] The powder according to the present invention is an aggregate of many particles. The material of the particles is a Co-based alloy. This alloy contains C, Cr, W, Si, Mn, Fe, and Ni. This alloy further contains Cu or Mo. The balance is Co and unavoidable impurities. The role of each element in this alloy will be described in detail below.

[0015] [Cobalt (Co)] Co is the main component of the matrix in the alloy. At room temperature, the stable crystal structure of Co alone is a hexagonal close packed structure (hcp). At temperatures of 690K or higher, the stable crystal structure of Co alone is a face-centered cubic lattice (fcc). In the powder according to the present invention, the matrix (at room temperature) is mainly a γ phase. This matrix may have an ε phase together with the γ phase. The crystal structure of the γ phase is fcc. The crystal structure of the ε phase is hcp.

[0016] [Carbon (C)] C combines with Cr and W to form carbides. These carbides can contribute to high hardness of the alloy. From this viewpoint, the C content is preferably 1.00 mass% or more, more preferably 1.30 mass% or more, and particularly preferably 1.50 mass% or more. Excess C impairs the toughness of the alloy. From the viewpoint of excellent toughness, the C content is preferably 3.00 mass% or less, more preferably 2.70 mass% or less, and particularly preferably less than 2.50 mass%.

[0017] Chromium Cr combines with C to form carbides. These carbides can contribute to the room temperature hardness, high temperature hardness, wear resistance, and corrosion resistance of the alloy. From these viewpoints, the Cr content is preferably 25.0 mass% or more, more preferably 27.0 mass% or more, and particularly preferably 28.0 mass% or more. Excess Cr impairs toughness. Furthermore, excess Cr leads to the formation of excess ε phase. This ε phase impairs the corrosion resistance of the molded product. From the viewpoints of toughness and corrosion resistance, the Cr content is preferably 34.0 mass% or less, more preferably 32.0 mass% or less, and particularly preferably 31.0 mass% or less.

[0018] [Tungsten (W)] W combines with C to form carbides. These carbides can contribute to high-temperature hardness and wear resistance. From these viewpoints, the W content is preferably 3.0 mass% or more, more preferably 6.0 mass% or more, and particularly preferably 8.0 mass% or more. Excess W impairs the toughness of the alloy. From the viewpoint of toughness, the W content is preferably 15.0 mass% or less, more preferably 12.0 mass% or less, and particularly preferably 10.0 mass% or less.

[0019] [Silicon (Si)] Si can contribute to the corrosion resistance and machinability of the alloy. From this viewpoint, the Si content is preferably 0.01 mass% or more, more preferably 0.20 mass% or more, and particularly preferably 0.50 mass% or more. Excessive Si impairs the toughness of the alloy. From the viewpoint of toughness, the Si content is preferably 2.00 mass% or less, more preferably 1.90 mass% or less, and particularly preferably 1.80 mass% or less.

[0020] [Manganese (Mn)] Mn generates a γ phase. This γ phase can contribute to the toughness of the alloy. From this viewpoint, the Mn content is preferably 0.01 mass% or more, more preferably 0.10 mass% or more, and particularly preferably 0.20 mass% or more. Excess Mn inhibits the strength of the alloy. From the viewpoint of strength, the Mn content is preferably 1.00 mass% or less, more preferably 0.80 mass% or less, and particularly preferably 0.60 mass% or less.

[0021] [Iron (Fe)] Fe can contribute to the workability of the molded product. From this viewpoint, the Fe content is preferably 0.01 mass% or more, more preferably 0.03 mass% or more, and particularly preferably 0.05 mass% or more. Excess Fe impairs the corrosion resistance of the alloy. From the viewpoint of corrosion resistance, the Fe content is preferably 10.0 mass% or less, more preferably 7.0 mass% or less, and particularly preferably 5.0 mass% or less. The Co-based alloy may not substantially contain Fe. In other words, the preferred Fe content is 0 mass% or more and 10.0 mass% or less.

[0022] [Nickel (Ni)] Ni dissolves in the matrix and enhances the corrosion resistance of the alloy. From this viewpoint, the Ni content is preferably 0.01 mass% or more, more preferably 0.03 mass% or more, and particularly preferably 0.05 mass% or more. Excess Ni inhibits the hardness of the alloy. From the viewpoint of hardness, the Ni content is preferably 15.0 mass% or less, more preferably 10.0 mass% or less, and particularly preferably 5.0 mass% or less. The Co-based alloy may not substantially contain Ni. In other words, the preferred Ni content is 0 mass% or more and 15.0 mass% or less.

[0023] [Copper (Cu) and Molybdenum (Mo)] Cu and Mo are important additive elements in the Co-based alloy according to the present invention. The Co-based alloy may have a composition that contains Cu but not Mo. The Co-based alloy may have a composition that contains Mo but not Cu. The Co-based alloy may have a composition that contains both Cu and Mo.

[0024] Copper (Cu) As is clear from the Co-Cu binary phase diagram, Cu is hardly dissolved in the Co matrix at room temperature. On the other hand, according to the knowledge obtained by the present inventor, in the alloy according to the present invention, about 2% of Cu can be dissolved in the matrix. Therefore, Cu can contribute to the corrosion resistance of the alloy. From this viewpoint, the Cu content is preferably 0.1 mass% or more, more preferably 0.5 mass% or more, and particularly preferably 1.0 mass% or more. According to the knowledge obtained by the present inventor, in an alloy with an excessive amount of Cu, a Cu phase precipitates. This Cu phase inhibits the hardness of the alloy. From the viewpoint of hardness, the Cu content is preferably 10.0 mass% or less, more preferably 3.5 mass% or less, and particularly preferably 2.0 mass% or less.

[0025] [Molybdenum (Mo)] Mo combines with C to form carbides. Mo can also dissolve in the matrix. According to the findings of the present inventors, carbides contribute to hardness and wear resistance. According to the findings of the present inventors, Mo dissolved in the matrix suppresses dissolution of the matrix in a hydrochloric acid environment and a hydrofluoric acid environment. In other words, Mo also contributes to corrosion resistance. From the viewpoints of hardness, wear resistance, and corrosion resistance, the Mo content is preferably 0.1 mass% or more, more preferably 0.5 mass% or more, and particularly preferably 1.0 mass% or more. Excess Mo inhibits the toughness of the alloy. From the viewpoint of toughness, the Mo content is preferably 15.0 mass% or less, more preferably 10.0 mass% or less, and particularly preferably 5.0 mass% or less.

[0026] [Total amount of Cu and Mo] From the viewpoint of corrosion resistance, the total amount of Cu and Mo is preferably 0.2 mass% or more, more preferably 1.0 mass% or more, and particularly preferably 1.5 mass% or more. From the viewpoint of alloy toughness, this total amount is preferably 25.0 mass% or less, more preferably 15.0 mass% or less, and particularly preferably 7.0 mass% or less.

[0027] [Mo / C] A part of Mo is consumed to form carbides, and the remaining Mo dissolves in the matrix. The ratio of the mass content of Mo to the mass content of C is preferably 1.3 or more. In a Co-based alloy in which this ratio is 1.3 or more, a sufficient amount of Mo dissolves in the matrix. This Co-based alloy has excellent corrosion resistance. From this viewpoint, this ratio is more preferably 1.8 or more, and particularly preferably 2.3 or more. This ratio is preferably 10.0 or less.

[0028] Oxygen In the Co-based alloy according to the present invention, O is an unavoidable impurity. From the viewpoint of the corrosion resistance of the alloy, the mass content of O is preferably 200 ppm or less, more preferably 150 ppm or less, and particularly preferably 100 ppm or less.

[0029] [Aluminum (Al)] In the alloy of the present invention, Al is an inevitable impurity. Al can combine with Ti or Ni to form an intermetallic compound. This intermetallic compound impairs the toughness of the alloy. From the viewpoint of toughness, the Al content is preferably 0.50 mass% or less, more preferably 0.40 mass% or less, and particularly preferably 0.35 mass% or less.

[0030] [Titanium (Ti)] In the alloy of the present invention, Ti is an inevitable impurity. Ti can combine with Al or Ni to form an intermetallic compound. This intermetallic compound impairs the toughness of the alloy. From the viewpoint of toughness, the Ti content is preferably 0.50 mass% or less, more preferably 0.40 mass% or less, and particularly preferably 0.35 mass% or less.

[0031] [Metal structure] The metal structure of Co-based alloys is as follows: (1) Matrix and (2) Carbides dispersed in this matrix This matrix (1) has the following structure: (1-1) γ phase, which has an fcc structure and / or (1-2) ε phase, which has the hcp structure Contains:

[0032] [ε phase] As described above, the matrix may have an ε phase. The ε phase has poor toughness. If the amount of the ε phase is excessive, the durability and machinability of the molded product are impaired. From these viewpoints, the volume fraction Pε of the ε phase (hcp structure) is preferably 60.0% or less of the entire metal structure, more preferably 40.0% or less, and particularly preferably 25.0% or less. The volume fraction Pε (%) is calculated by the following formula. Pε = Xε 100 In this formula, Xε is the volume ratio of the ε phase. The volume ratio Xε is calculated by the following formula.

[0033]

number

[0034] [carbide] The metal structure of Co-based alloys may contain the following carbides (2): (2-1) M6C carbide (2-2)M7C3 carbide and (2-3)M23C6 carbide Examples of M6C-based carbides include Co3W3C. Examples of M7C3-based carbides include Cr7C3. Examples of M23C6-based carbides include Cr23C6. The metal structure may include all of the M6C-based carbides, M7C3-based carbides, and M23C6-based carbides, or may include any two of them, or may include any one of them.

[0035] M6C carbides, M7C3 carbides and M23C6 carbides are not easily dissolved in hydrofluoric acid. An alloy containing an appropriate amount of these carbides has excellent corrosion resistance. From the viewpoint of corrosion resistance, the total volume ratio Pc of M6C carbides, M7C3 carbides and M23C6 carbides to the entire metal structure is preferably 12.0% or more, more preferably 15.0% or more, and particularly preferably 20.0% or more. Excessive carbides impair the toughness of the alloy. From the viewpoint of toughness, the volume ratio Pc is preferably 50.0% or less, more preferably 40.0% or less, and particularly preferably 35.0% or less. The volume ratio Pc (%) is calculated by the following formula. Pc = Xc 100 In this formula, Xc is the volume ratio of carbide. The volume ratio Xc is calculated by taking a backscattered electron image of the cross-sectional structure of the compact obtained from the powder. Image analysis software is used for this calculation.

[0036] [Alloy manufacturing] The Co-based alloy according to the present invention can be produced by a melting method, a casting method, a powder metallurgy method, etc. From the viewpoint of toughness of the alloy, the powder metallurgy method is preferable, and the atomization method is particularly preferable. EXAMPLES

[0037] The effects of the present invention will be clarified by the following examples, but the present invention should not be construed as being limited based on the description of these examples.

[0038] [Examples 1-30 and Comparative Examples 34-48] A metal having a predetermined composition was melted to obtain a molten metal. The molten metal was melted in an inert gas atmosphere and subjected to nitrogen gas atomization to obtain a powder. The powder was subjected to classification to adjust the particle size to 500 μm or less. The powder was filled into a capsule, and the capsule was sealed. The powder was subjected to hot isostatic pressing (HIP) at 1170° C. to obtain the bulks of Examples 1-30 and Comparative Examples 34-48.

[0039] [Examples 31-33] The bulk of Examples 31-33 was obtained by an arc melting method.

[0040] [hardness] The bulk Rockwell hardness (HRC) was measured and the results are shown in Tables 1-4 below. A hardness of 45 HRC or greater is preferred.

[0041] [Shock value] A test piece (10R2mmC notch) was obtained from the bulk. The test piece was subjected to a Charpy impact test to measure the impact value. The results are shown in Table 1-4 below. The impact value was 5J / cm 2 More preferably, the above is true.

[0042] [Corrosion resistance] A test piece (10 mm x 10 mm x 14 mm) was obtained from the bulk. This test piece was subjected to a corrosion resistance test. The test conditions were as follows. Solution: 10% hydrochloric acid aqueous solution Temperature: 40℃ Duration: 10 hours The corrosion rate was calculated by dividing the corrosion weight loss by the surface area of ​​the test piece before the test and the time. The results are shown in Table 1-4 below. 2 It is preferable that the thickness is less than or equal to .h.

[0043] [Table 1]

[0044] [Table 2]

[0045] [Table 3]

[0046] [Table 4]

[0047] In the alloy of Comparative Example 34, the volume fraction Pc of carbides is small because the amount of C is too small, and therefore the hardness of this alloy is insufficient.

[0048] In the alloy according to Comparative Example 35, the volume fraction Pc of carbides is large because of an excess of C. Therefore, the toughness of this alloy is insufficient.

[0049] The alloy according to Comparative Example 36 has an insufficient Cr content, and therefore the hardness and corrosion resistance of this alloy are insufficient.

[0050] The alloy according to Comparative Example 37 contains an excessive amount of Cr, and therefore the toughness of this alloy is insufficient.

[0051] In the alloy of Comparative Example 38, the volume fraction Pc of carbides is small because the amount of W is too small, and therefore the hardness of this alloy is insufficient.

[0052] In the alloy of Comparative Example 39, the volume fraction Pc of carbides is large because of the excessive amount of W. Therefore, the toughness of this alloy is insufficient.

[0053] The alloy of Comparative Example 40 does not substantially contain Si, and therefore the hardness of this alloy is insufficient.

[0054] The alloy according to Comparative Example 41 contains an excess of Si, and therefore the toughness of this alloy is insufficient.

[0055] The alloy of Comparative Example 42 does not substantially contain Mn, and therefore the hardness of this alloy is insufficient.

[0056] In the alloy of Comparative Example 43, Mn is excessive, and therefore the toughness of this alloy is insufficient.

[0057] In the alloy of Comparative Example 44, Fe is excessive, and therefore the corrosion resistance of this alloy is insufficient.

[0058] In the alloy of Comparative Example 45, Ni is excessive, and therefore the hardness of this alloy is insufficient.

[0059] The alloy of Comparative Example 46 contains an excess of ε phase because it does not substantially contain Cu and Mo. Therefore, this alloy does not have sufficient corrosion resistance.

[0060] In the alloy of Comparative Example 47, Cu is excessive, and therefore the hardness of this alloy is insufficient.

[0061] In the alloy of Comparative Example 48, Mo is excessive, so the volume fraction Pc of carbides is large, and therefore the toughness of this alloy is insufficient.

[0062] The alloys according to Examples 1-33 are excellent in various properties. From these results, the superiority of the present invention is clear. [Industrial Applicability]

[0063] The Co-based alloys described above are suitable for a variety of applications requiring corrosion resistance.

Claims

1. C: 1.00% by mass or more and 3.00% by mass or less, Cr: 25.0% by mass or more and 34.0% by mass or less, W: 3.0% by mass or more and 10.0% by mass or less, Si: 0.01% by mass or more and 2.00% by mass or less, Mn: 0.01% by mass or more and 1.00% by mass or less, Fe: 10.0% by mass or less Ni: 15.0% by mass or less Cu: 0.1% by mass or more and 10.0% by mass or less and Mo: 0% by mass or more and 15.0% by mass or less and the balance being Co and unavoidable impurities.

2. 2. The Co-based alloy according to claim 1, wherein the volume fraction Pε of the ε phase having an hcp structure with respect to the entire metal structure is 60.0% or less.

3. The metal structure is (1) Matrix and (2) Carbide dispersed in the matrix It has The matrix (1) is (1-1) γ phase, which is a phase having an f.c.c. structure and / or (1-2) ε phase, which is a phase having an h.c.p. structure Contains The carbide (2) (2-1) M6C carbide (2-2) M7C3 carbide and (2-3) M23C6 carbide The composition includes one or more selected from the group consisting of 3. The Co-based alloy according to claim 1, wherein a volume fraction Pc of the carbides relative to the entire metal structure is 12.0% or more and 50.0% or less.

4. The Co-based alloy according to claim 1 , wherein the ratio of the Mo content to the C content is 1.3 or more.

5. The material is a Co-based alloy, The Co-based alloy is C: 1.00% by mass or more and 3.00% by mass or less, Cr: 25.0% by mass or more and 34.0% by mass or less, W: 3.0% by mass or more and 10.0% by mass or less, Si: 0.01% by mass or more and 2.00% by mass or less, Mn: 0.01% by mass or more and 1.00% by mass or less, Fe: 10.0% by mass or less Ni: 15.0% by mass or less Cu: 0.1% by mass or more and 10.0% by mass or less and Mo: 0% by mass or more and 15.0% by mass or less and the balance being Co and unavoidable impurities.

Citation Information

Patent Citations

  • Three-dimensional printing direct manufacturing method of engine cylinder head valve seat

    CN104874793A

  • 3D printing based method for preparing antibacterial cobalt based dental crown

    CN105838926A

  • Cast cobalt alloy

    JP1981102542A

  • Co base alloy for building up

    JP1987289397A

  • Drawing method for stellite

    JP1991071912A